2013
DOI: 10.3390/ijerph10020541
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Levels of Airborne Bacteria, Gram-Negative Bacteria, and Fungi in Hospital Lobbies

Abstract: Aims: We assessed the levels of airborne bacteria, Gram-negative bacteria (GNB), and fungi in six hospital lobbies, and investigated the environmental and hospital characteristics that affected the airborne microorganism levels. Methods: An Andersen single-stage sampler equipped with appropriate nutrition plate agar was used to collect the samples. The three types of microorganisms were repeatedly collected at a fixed location in each hospital (assumed to be representative of the entire hospital lobby) from 08… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
4
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 13 publications
6
58
4
2
Order By: Relevance
“…Our study observed maximum bio-load during the rainy season in different ICUs in contrast to Park et al [9], due to the location of our hospital in tropical area where extreme monsoon persists for 5-6 months in a year with the high amount of moisture and humidity in the air responsible for generation of more bio-aerosols. Similar to us, several studies demonstrated the presence of more Grampositive organisms than Gram-negative in the air of the ICUs [10].…”
Section: Discussioncontrasting
confidence: 53%
“…Our study observed maximum bio-load during the rainy season in different ICUs in contrast to Park et al [9], due to the location of our hospital in tropical area where extreme monsoon persists for 5-6 months in a year with the high amount of moisture and humidity in the air responsible for generation of more bio-aerosols. Similar to us, several studies demonstrated the presence of more Grampositive organisms than Gram-negative in the air of the ICUs [10].…”
Section: Discussioncontrasting
confidence: 53%
“…The concentration of bioaerosols in the ORs after sterilization and disinfection might be due to high humidity (more than 60% after sterilization), occupants’ density, HEPA filters needing to be replaced, poor ventilation, air changes per hour being less than standard levels (15 h −1 ) (Dharan and Pittet, 2002; Streifel, 1999), inadequate disinfection, UV irradiation in short time (less than 2 h), and hospital building’s age. Among these factors, humidity, insufficient disinfection, UV irradiation, and the lack of proper ventilation were most responsible for the number of fungi and bacteria aerosols after sterilization (Chow and Yang, 2005; Dharan and Pittet, 2002; Friberg et al, 1999; Hoffman et al, 2002; Park et al, 2013; Tesfaye et al,2015). Park et al (2013), Tesfaye et al (2015) and Hoffman et al (2002) showed that the lack of proper ventilation, moisture, and unfiltered air were most responsible for microbial growth in hospital wards, which is in line with the findings of the present research (Dharan and Pittet, 2002; Hoffman et al, 2002; Park et al, 2013; Tesfaye et al,2015).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, fungal bioaerosols can be caused colonizing syndromes, such as nosocomial aspergillosis and allergic bronchopulmonary aspergillosis (Ortiz et al, 2009; Sohrabi et al, 2014). The presence of fungi in hospital wards, particularly ORs, is linked to several factors such as the (i) presence, condition, and activities of patients, (ii) temperature, (iii) inadequate ventilation, (iv) poor air-conditioning systems, (v) humidity, (vi) organic matter (OM) available in materials of walls, (vii) types of surgery, (viii) the season, and (ix) inadequate disinfection (Dharan and Pittet, 2002; Faure et al, 2002; Nourmoradi et al, 2012; Park et al, 2013; Sautour et al, 2007; Wan et al, 2011). The main reason for bacterial contamination in OR air is thought to be surgical site infection after operations (Dharan and Pittet, 2002; Landrin et al, 2005; Napoli et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These can be the occupants themselves and their activities . Other factors influencing the microbial population include building maintenance, cleanliness, indoor temperature and relative humidity, type of furniture, and carpeting (Ross et al, 2004;Mandal and Brandl, 2011;Park et al, 2013).…”
Section: Introductionmentioning
confidence: 99%